Media Daring sebagai Self Directed Learning Materi PAI SD Pada Masa Pandemi Covid-19 - Munir, Misbahul; Supriyatno, Triyo (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2020)
The purpose of this research is to offer alternative media based on independent learning during the pandemic covid 19. The first objective is to explore information on online network-based media that is widely used in Indonesia as a support for learning; Second, to search a model of self-directed learning theory that has characteristics according to research needs; Third, to provide an overview of the alternative characteristics of online-based learning media offered. The data in this study were taken through google schoolar, semantic scholar, elsevier, researchgate, online seminars via youtube, zoom. The results of this study the most widely used media in Indonesia are Youtube, Facebook, WhatsApp, Zoom, Google Classroom. While the theory taken related to self directed learning according to Song and Hill’s, The typology of youtube, facebook, whatsapp, zoom, and google classroom media is found to be opened, closed, open and closed combination for the public. All media have in common can share files in the form of video, word, pdf. Except youtube and zoom. The benefit of Youtube is the flexibility of time and content developed with audio visual, while zooming does not have the flexibility of time, learning can be presented interactively between teachers and students.